Study on heating model and heat transfer law of anti-oxidation coating materials in high vacuum environment - Dongyang An; Jingmin Dai; Peng Xiao (Results in Physics, 2019)
On the basis of resistance direct heating method, a wide-temperature-range (773–2573 K) and high-vacuum heating apparatus for anti-oxidation coatings materials is built. The heat transfer model of coating materials is deduced by the heat transfer principle. By COMSOL numerical analysis, the relationship between heat transfer, heat distribution, extreme value of temperature and power voltage, power time, diameter of surface defects is studied. The results show that the heat coupling effect causes the maximum temperature in the central area. Both centre part temperature and the maximum temperature increase and tend to be stable with the rise of voltage, time and the diameter of surface defects. When the time reaches the 30 s and the voltage is 1.9 V, the maximal temperature is about 2600 K, 5 K higher than central part temperature. When the electric voltage is from 1.5 V to 2 V, the maximum temperature of the iridium coating surface varies from 2300 K to the melting point (2719 K). With a 1.9 V electric voltage, the diameter of surface defects varies from 0.5 × 10−3 to 3 × 10−3 m and the maximal surface temperature varies from 2583 K to 2610 K. In the study, the present work aims to reveal the heat transfer law of anti-oxidation coatings materials and play an active role in failure and reliability research of the materials, which will speed up the research development of engineering application. Keywords: Rhenium and iridium material, Test apparatus, Heating model, Heat transfer, Defect